Near-Infrared–Guided Pulmonary Segmentectomy After Endobronchial Indocyanine Green Injection - Wada, Hironobu; Yamamoto, Takayoshi; Morimoto, Junichi; Sakairi, Yuichi; Suzuki, Hidemi; Nakajima, Takahiro; Yoshino, Ichiro (The Annals of Thoracic Surgery, 2020)
The aim of this study is to prospectively determine the feasibility and safety of near-infrared fluorescence-guided pulmonary segmentectomy after endobronchial indocyanine green (ICG) injection using virtual bronchoscopy. Fifteen patients who underwent pulmonary segmentectomy were prospectively enrolled. Using preoperative computed tomography datasets a bronchial road map was created to determine the bronchus for ICG injection. Immediately after intubation ICG was injected into the target bronchi using an ultrathin bronchoscope. During the operation a near-infrared thoracoscope was used to detect ICG fluorescence and determine the intersegmental plane. The assessment points were (1) whether the ICG demarcation lines corresponded to the intersegmental lines expected from the pulmonary veins, (2) whether it was possible for the planned segmentectomy to be completed by electrocautery and 1 or fewer uses of an automated suturing device according to the demarcation plane, (3) whether any surgical complications occurred intraoperatively or (4) in the 1 month after surgery, and (5) whether the target lesion was removed completely with sufficient surgical margin to evaluate the feasibility and safety of this procedure. In 13 cases (87%) a segmentectomy was completed in the planned way with sufficient surgical margins. The failure in 2 cases was due to a technical issue in the bronchial injection. No complications developed intraoperatively. Recurrent air leakage occurred in 1 case. No procedure-related adverse event was noted postoperatively. Near-infrared–guided pulmonary segmentectomy with endobronchial ICG injection using virtual bronchoscopy was safe and feasible, and minor technical revision can make this procedure more reliable.